Effect of Household Catastrophic Health Expenditure on Vulnerability to Poverty in Ghana - Bandoh, H.A (University of Ghana, 2016)
Background: Households are exposed to a wide range of shocks on a daily basis which can reduce their consumption pattern and threaten their welfare. Households are also likely to be vulnerable to poverty due to health spending. In seeking health care services, households may face financial hardship termed Catastrophic Health Expenditure (CHE). This may not only lead to poverty but make the household vulnerable to future poverty. Objective: The main objective was to estimate the effect of catastrophic health expenditure on vulnerability to poverty among households in Ghana. Methods: Vulnerability is estimated using Chaudhuri’s Econometric model and for CHE the WHO method is used at thresholds of 5% and 20%. Data was sourced from the sixth round of the Ghana Living Standards Survey, a nationally representative sample of 16,772 households. The effect of CHE on household vulnerability to poverty was estimated using multivariate regression analysis. Key findings: The key findings show that overall, vulnerability to poverty estimates are higher, 34% compared to the current poverty estimate of 24.2%. The incidence of catastrophic health expenditure ranged between 0.45% to 24.96% and 5.24% to 25.55% depending on the method and threshold used. Vulnerability was significantly associated with CHE and some household socioeconomic characteristics. Conclusion: Therefore there’s a need to incorporate vulnerability in healthcare financing strategies and current poverty estimates to ensure financial/social protection of households from future poverty in Ghana.
Thesis(MPH)-University of Ghana,2016
Keywords: Household Catastrophic Health Expenditure; Poverty; Ghana